2009
DOI: 10.1007/s10916-009-9369-3
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Disease Diagnosis Using Artificial Neural Network Trained with Genetic Algorithm

Abstract: Tuberculosis is a common and often deadly infectious disease caused by mycobacterium; in humans it is mainly Mycobacterium tuberculosis (Wikipedia 2009). It is a great problem for most developing countries because of the low diagnosis and treatment opportunities. Tuberculosis has the highest mortality level among the diseases caused by a single type of microorganism. Thus, tuberculosis is a great health concern all over the world, and in Turkey as well. This article presents a study on tuberculosis diagnosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…The authors compared their results with previous studies of [62] and [74], who have reported accuracy of 92.30% and 77% respectively. The results of [85] were better than [75], a study on BPwM with two hidden layers classification, which reported accuracy of 93.93%. Reference [85] could not compare their result with [75] on Levenberg-Marquardt (LM) algorithm, because of the complexity of the algorithm.…”
Section: Genetic Algorithmmentioning
confidence: 79%
See 3 more Smart Citations
“…The authors compared their results with previous studies of [62] and [74], who have reported accuracy of 92.30% and 77% respectively. The results of [85] were better than [75], a study on BPwM with two hidden layers classification, which reported accuracy of 93.93%. Reference [85] could not compare their result with [75] on Levenberg-Marquardt (LM) algorithm, because of the complexity of the algorithm.…”
Section: Genetic Algorithmmentioning
confidence: 79%
“…The results of [85] were better than [75], a study on BPwM with two hidden layers classification, which reported accuracy of 93.93%. Reference [85] could not compare their result with [75] on Levenberg-Marquardt (LM) algorithm, because of the complexity of the algorithm. The authors concluded that their classification accuracy for diagnosing TB with GA's is better than previous studies.…”
Section: Genetic Algorithmmentioning
confidence: 79%
See 2 more Smart Citations
“…On the one hand, artificial neural networks have been successfully used in understanding the heterogeneous manifestations of asthma [7], diagnosing tuberculosis [8], classifying leukaemia [9], detecting heart conditions in ECG data [10], etc. These studies show that neural networks have been proven to be capable of dealing with complicated medical data such as the ambiguous nature of the ECG signal data, where neural networks show some outstanding results compared to other methods.…”
Section: Introductionmentioning
confidence: 99%